Deteksi Kadar Alkohol Dalam Tubuh Manusia - Suparlan, Fumio Highy; Jusak, Jusak; Resmana, Susianto Tri (Jurnal GEMATIKA, 2009)
Every year the number of motor vehicles increased street-traffic, this wil only cause the traffic accident rate higher street traffic. The reasons vary, one cause was an accident caused by drivers who drive a motor vehicle in a state affected by alcohol or in other words drunk driving. TGS 2620 sensor is one sensor that can detect alcohol content in the air, with the help of data from the sensor microcontroler can be sent to a computer and then processed in order to display the output in units of parts per milion (PPM). Research successfuly detected at levels of alcohol in the human body with 1.2236% error rate.